Making good cider out of bad apples -Signaling expectations boosts cooperation among would-be free riders - Nagatsu, Michiru; Larsen, Karen; Karabegovic, Mia; Székely, Marcell; Mønster, Dan; Michael, John (Judgment and Decision Making, 2018)
The present study investigates how group-cooperation heuristics boost voluntary contributions in a repeated public goods game. We manipulate two separate factors in a two-person public goods game: i) group composition (Selfish Subjects vs. Conditional Cooperators) and ii) common knowledge about group composition (Information vs. No Information). In addition, we let the subjects signal expectations of the other's contributions in the experiment's second phase. Common knowledge of Selfish type alone slightly dampens contributions but dramatically increases contributions when signaling of expectations is allowed. The results suggest that group-cooperation heuristics are triggered when two factors are jointly salient to the agent: (i) that there is no one to free-ride on; and (ii) that the other wants to cooperate because of (i). We highlight the potential effectiveness of group-cooperation heuristics and propose solution thinking as the schema of reasoning underlying the heuristics. The high correlation between expectations and actual contributions is compatible with the existence of default preference to satisfy others' expectations (or to avoid disappointing them), but the stark end-game effect suggests that group-cooperation heuristics, at least among selfish players, function ultimately to benefit material self-interest rather than to just please others.